Enhancing economic self-reliance by promoting the development of local traditional herbal medicine as a flagship product - Adi Santoso; Nanang Cendriono (Universitas Muhammadiyah Magelang, 2024)
Muhammadiyah branches and sub-branches, present in every sub-district and village, play a pivotal role in enhancing community welfare and ensuring equitable distribution of resources. To foster economic self-reliance, these units must establish business ventures capable of sustaining organizational operations and generating employment opportunities. The Muhammadiyah Sub-branch of Singosaren, Ponorogo Regency, has been our partner in this community service project. Through this initiative, non-productive members of the Singosaren sub-branch have developed new skills in producing hygienic herbal medicine following Good Manufacturing Practices (GMP). Moreover, participants have gained essential soft skills in digital marketing to promote their products online.